Ophthalmological abnormalities in Dubowitz Syndrome - Soares, Andreia (2017)
Introduction: Dubowitz syndrome is a rare autosomal recessive disorder characterized by several congenital abnormalities, which include a wide range of both external and intraocular ophthalmologic deformities. We present a case report of a patient with Dubowitz Syndrome. Case report: A 3-year-old boy with Dubowitz syndrome was referred for ophthalmology consultation. The external ophthalmological examination showed bilateral blepharophimosis/ptosis, telecanthus and epicanthic folds. Cycloplegic retinoscopy revealed high hyperopia (+ 8.00 diopters) and the patient had convergent strabismus. Biomicroscopy and fundus examination were normal. Discussion/Conclusion: Dubowitz syndrome should be considered in the differential diagnosis of syndromes that present with the described external ophthalmological malformations. The ophthalmologist has to refer these patients to a specialized group able to integrate these anomalies with other systemic deformities, allowing a correct diagnosis and proper treatment.